2020
DOI: 10.3389/fpsyg.2020.01543
|View full text |Cite
|
Sign up to set email alerts
|

Finger Sequence Learning in Adults Who Stutter

Abstract: Originary neurogenic, non-syndromatic stuttering has been linked to a dysfunctional sensorimotor system. Studies have demonstrated that adults who stutter (AWS) perform poorly at speech and finger motor tasks and learning (e.g., Smits-Bandstra et al., 2006b; Namasivayam and van Lieshout, 2008). The high relapse rate after stuttering treatment could be a further hint for deficient motor learning and, in particular, for the limited generalization of the learned technique in daily communication. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…This was supported by a later study of the learning of non-words in adults (Namasivayam and van Lieshout, 2008). However, these results were contradicted by two recent studies of finger sequence learning, in adults (Korzeczek et al, 2020) and children (Tendera et al, 2020), reporting no group difference in sequence learning. Instead, the latter study found indications of more general fine motor difficulties.…”
Section: Automatization Of Motor Sequences and Speechmentioning
confidence: 77%
“…This was supported by a later study of the learning of non-words in adults (Namasivayam and van Lieshout, 2008). However, these results were contradicted by two recent studies of finger sequence learning, in adults (Korzeczek et al, 2020) and children (Tendera et al, 2020), reporting no group difference in sequence learning. Instead, the latter study found indications of more general fine motor difficulties.…”
Section: Automatization Of Motor Sequences and Speechmentioning
confidence: 77%
“…Falk et al ( 2015 ) investigated timing control in finger tapping to periodic tone sequences and a musical beat and showed that children and adolescents who stutter showed poorer synchronization to both metronome and musical stimuli than fluent controls. Conversely, some recent studies have reported no differences in finger sequence learning (Korzeczek et al, 2020 ) or manual tasks using the Purdue Pegboard Test (Werle et al, 2019 ).…”
Section: Introductionmentioning
confidence: 95%